IMPLEMENTASI METODE CERTAINTY FACTOR PADA SISTEM PAKAR DIAGNOSIS MASALAH KULIT WAJAH BERBASIS WEBSITE - khurotul aini; Galuh saputri (LPPM Universitas Abdurrab, 2026)
Facial skin problems are common health conditions that can reduce quality of life and self-confidence. At least 12 types of facial skin disorders are commonly encountered in beauty clinics, including dermatitis, xerosis cutis, acne vulgaris, hyperpigmentation, and rosacea. Limited access to medical services, busy schedules, and cost considerations prevent many people from directly consulting dermatologists. This study aims to build a web-based expert system using the Certainty Factor method to support early identification of facial skin disorders based on 20 compiled symptoms. System development adopted the Extreme Programming (XP) methodology, and the system was designed to produce diagnostic output along with relevant treatment recommendations based on symptoms reported by users. Expert confidence weights were obtained through interview sessions with medical staff at Naavagreen Clinic Pamulang. System usability evaluation was conducted using the System Usability Scale (SUS) method involving 78 respondents. The SUS score of 73.49 falls into the acceptable category, indicating that this system is suitable fo use as a supporting tool for early self-detection of facial skin problems